Clear-Sky Surface Solar Radiation During the South China Sea Monsoon Experiment - 林博雄(Po-Hsiung Lin); 周明達(Ming-Dah Chou); 姬強(Qiang Ji); 蔡錫祺Si-Chee Tsay (TAO : Terrestrial, atmospheric, and oceanic sciences, 2002)
Downward total solar fluxes measured at Dungsha coraisland (20¢X42'N, 116¢X43'E) during the South China Sea Monsoon Experiment (May-June 1998) have been calibrated and compared with radiative transfer calculations for three clear-sky days. Model calculations use water vapor and temperature profiles from radiosonde measurements, and the aerosol optical thickness is derived from radiosonde measurements, and the aerosol optical thickness is derived from sunphotometric radiance measurements. Results show that the difference between observed and model-calculated downward surface fluxes is < 3% of the daily mean. Averaged downward surface fluxes from observations and calculations for the three selected dates are 314 and 317 W/m2, respectively. This result is consistent with a previous study using TOGA COARE measurements, which found good agreement between observations and model calculations. This study provides an extra piece of useful information for the modeling of radiative transfer, which helps to fill in the puzzle of the absorption of solar radiation in the atmosphere.